Design guidelines for healing gardens in the general hospital - Wang, Quying; Tzortzi, Julia Nerantzia (Frontiers in Public Health, 2023)
Healing Gardens have been identified as a cost-effective and efficient way to improve physical and mental health, but they have not received adequate attention and have not been popularized, particularly in China. This paper aims to provide a new perspective and guidelines for implementing healing gardens in general hospitals. To achieve this, a methodology is proposed for defining guidelines for a specific general hospital, which includes extracting features of successful healing gardens from case studies, defining key components based on theoretical frameworks, confirming essential features through user questionnaires, and conducting site analyses to arrive at conclusions. The methodology has been applied to a case study of Zhongnan Hospital in Wuhan. This research offers a novel perspective and methodology for implementing Healing Gardens in general hospitals, with the potential to improve physical and mental health in a cost-effective and efficient manner. It is our hope that this work will encourage more hospitals to develop Healing Gardens as preventive medical tools.